Nutrition status in adult Chilean population: economic, ethnic and sex inequalities in a post-transitional country. (5th August 2020) - Mujica-Coopman, María F; Navarro-Rosenblatt, Deborah; López-Arana, Sandra; Corvalán, Camila
Abstract: Objective: To assess the relationship between malnutrition, socioeconomic status (SES) and ethnicity in Chilean adult population. Design: Nationally representative survey (ENS) conducted in 2016–2017. Sociodemographic information, weight, height and hemoglobin (Hb) were measured (2003 ENS). Excess weight was defined as BMI ≥25 kg/m 2 . Undernutrition included underweight (BMI <18·5 kg/m 2 ), short stature (height <1·49 m in women and <1·62 m in men) or anaemia (Hb <12 g/l). Education and household income level were used as indicators of SES; ethnicity was self-reported. We applied linear combinations of estimators to compare the prevalence of excess weight and undernutrition by SES and ethnicity. Setting: Chile. Participants: In total, 5082 adults ≥20 years (64 % women) and 1739 women ≥20 years for anaemia analyses. Results: Overall, >75 % of women and men had excess weight. Low SES women either by income or education had higher excess weight ((82·0 (77·1, 86·1) v. 65·0 (54·8, 74·1)) by income; (85·3 (80·6, 89·0) v. 68·2 (61·6, 74·1) %) by education) and short stature (20–49 years; 31(17·9, 48·2) v. 5·2 (2·2, 11·4) by education); obesity was also more frequent among indigenous women (20–49 years; 55·8 (44·4, 66·6) v. 37·2 (32·7, 42·0) %) than non-indigenous women. In men, excess weight did not significantly differ by SES or ethnicity, but short stature concentrated in low SES (20–49 years; 47·6 (24·6, 71·6) v. 4·5 (2·1, 9·5) by education) and indigenous men (21·5 (11·9, 5·5, 11·9) v. 8·2 (5·5, 11·9)) ( P < 0·05 for all). Conclusions: In Chile, malnutrition is disproportionately concentrated among women of low SES and indigenous origin; these inequalities should be considered when implementing prevention policies.